(untitled) (River Edge, NJ, 2002)
A collection of original papers on microlocal analysis, Fourier analysis in the complex domain, generalized functions and related topics.
Keywords: Fourier analysis,Microlocal analysis,Functions of complex variables,Giải tích Fourier,Giải tích Microlocal,Hàm biến phức